FAKTOR - FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN RISIKO PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2017) - Salma Khairunnisa Gotri; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
This study aims to examine the factors that influence the disclosure of corporate risks, such as company size, sector type, level of risk , board size, and composition of the board of commissioners. The population in this study consisted of all companies listed on the Indonesia Stock Exchange in 2017. Sampling was done using the purposive sampling method. Total sample in this research was 326 companies. This study uses multiple regression analysis to test hypotheses. The results of this study indicate that not all factors studied such as company size, type of sector, level of risk, board size, and composition of board of commissioners have a significant effect on corporate risk disclosure.